The Uses of “tú” and “Ud.” in Speech Acts: An Approximation to the Bilingual’s Pragmatics (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This paper explores how second and third generation Cuban Americans fromMiami, Florida, use the address pronouns “tú” and “Ud.” when formulating speech acts such as requests in Spanish. A qualitative analysis shows that the explicit use of the pronouns when uttering a speech act fulfills a double purpose: 1) to flatter the hearer and express solidarity towards her/him, and 2) to establish distance towards the interlocutor when the speaker is in a position of power.
Keywords: Politeness; address pronouns bilingual Cuban Americans